1992
DOI: 10.1111/j.1365-2125.1992.tb04055.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition of flurbiprofen in uraemic patients.

Abstract: 1 Both single and multiple oral doses of 50 mg racemic flurbiprofen were given to eight patients with mild to moderate renal impairment. The plasma and urine concentrations of the R-and S-enantiomers of flurbiprofen and its major metabolites were measured by a stereoselective h.p.l.c. assay. 2 For R-flurbiprofen the oral clearance (mean ± s.d.: 38.3 ± 12.8 vs 30.8 ± 11.5 ml min-1) and volume of distribution (V.; 17.6 ± 3.9 vs 14.6 ± 2.5 1) were significantly greater (P < 0.05) than for the S-enantiomer. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
(29 reference statements)
4
18
0
Order By: Relevance
“…In the present study, the mean plasma concentration was 3331 ng ml -1 in the patients receiving orally administered flurbiprofen. This result is comparable with the previous data [9,[11][12][13][14]. Concerning topical application with the same two tapes as used in the present study, it was reported that the Cmax in the plasma was 870 ng ml -1 at the tmax of 11.6 h [8].These data are also comparable with the present result (1369 ng ml -1 ) on the plasma concentration in the patients receiving topically applied flurbiprofen.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, the mean plasma concentration was 3331 ng ml -1 in the patients receiving orally administered flurbiprofen. This result is comparable with the previous data [9,[11][12][13][14]. Concerning topical application with the same two tapes as used in the present study, it was reported that the Cmax in the plasma was 870 ng ml -1 at the tmax of 11.6 h [8].These data are also comparable with the present result (1369 ng ml -1 ) on the plasma concentration in the patients receiving topically applied flurbiprofen.…”
Section: Discussionsupporting
confidence: 83%
“…After oral administration of a tablet containing 40 mg flurbiprofen, the Cmax in the plasma was 5600 ng ml -1 and the tmax was 1.4 h [9]. After oral administration of a tablet containing 50 mg flurbiprofen, several studies reported that the Cmax ranged from 4200 to 8200 ng ml -1 and that the tmax ranged from 1.3 to 2.8 h [11][12][13][14]. In the present study, the mean plasma concentration was 3331 ng ml -1 in the patients receiving orally administered flurbiprofen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the presence of the 'futile cycle', renal dysfunction should cause greater elevations in AUCu for those drugs (such as ketoprofen) cleared predominantly by acyl-glucuronidation relative to drugs subject to significant phase I (non-conjugative) metabolism. This might explain why Knadler and associates [24] were unable to demonstrate 'futile cycling' based upon measurement of unbound flurbiprofen enantiomers in uraemic patients, since elimination of this drug proceeds by substantial oxidative metabolic pathways in addition to glucuronide conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with flurbiprofen [24,32] have shown a decrease in plasma protein binding of both enantiomers in uraemic patients, compared with normal subjects, which was attributed to a significantly lower plasma albumin concentration in the former. Some of our patients (none of whom was clinically uraemic) had serum albumin concentration values below the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation